Modeling the Inhibition of Vibrio cholerae Non-01 in Trypticase Soy Broth by Chitosan of Low and High Molecular Weight - Paredes-Aguilar, Maria de la Cruz; Avila-Sosa, Raul; Nevárez-Moorillón, Guadalupe V. (Frontiers in Marine Science, 2017)
Chitosan has proved to have antimicrobial properties, which can be used to protect seafood from contamination and growth of pathogens such as Vibrio cholerae. The aim of this study was to model the inhibition of Vibrio cholerae Non-01 by low and high molecular weight chitosan. Chitosan of low (LMWC) and high (HMWC) molecular weight (15 and 32 KDa respectively) was used at final concentrations of 600 and 1,000 mg/L and antimicrobial assays were carried out at temperatures of 5 and 35°C. Data were fitted to the Weibull distribution and b and n values were used to plot resistance frequency curves. Inhibition curves showed that the four treatments were effective at 5ºC, with 5.5 log reduction after 312 h with the highest chitosan concentration tested, while the effect of the 600 mg/L chitosan concentration was bacteriostatic rather than bactericidal (3.5 log reduction at 388 h). The 1,000 mg/L chitosan concentration was bactericidal at 35°C (6 log reduction) at a shorter time (12 h). No differences were observed by the different molecular weight of the chitosan used. Weibull model fit adequately (R2>0.8908) with experimental data, the highest cellular damage occurs significantly (p<0.05) with high chitosan concentrations regardless of molecular weight and treatment temperature. Resistance frequency plots showed a greater resistance of LMWC, with the maximum values of V. cholerae Non-01 resistance presented in the first minutes of the treatments regardless of the temperature.